Investigating Czech society’s expectations for forest recreation - Purwestri, Ratna Chrismiari; Hájek, Miroslav; Palátová, Petra; Tahri, Meryem; Huertas-Bernal, Diana Carolina; Awuni, Stephen; Letsoin, Sri Murniani Angelina; Rahmawan, Fajar; Hochmalová, Miroslava; Jarský, Vilém; Riedl, Marcel; Dudík, Roman (Frontiers in Forests and Global Change, 2025)
Forests provide numerous advantages for human wellbeing, i.e., provisioning, regulation, and cultural services. As part of the cultural services, recreational functions contribute aesthetic value and opportunities for various sports and leisure activities. Our research aims to address four main objectives: exploring respondents’ expectations regarding the naturalness of forest visuals and descriptions, investigating the relationship between forest visuals and public expectations of naturalness and facilities, and examining the independent predictors of high preferences in forest visuals (stand type, level of visual penetration, and occurrence of natural deadwood). Data regarding public expectations for forest recreation were collected through a representative online survey in the Czech Republic in 2022 among respondents aged 18 to 65 years. Vegetation density, derived from the Normalized Difference Vegetation Index for the forest area in 2018, was developed using CORINE Land Cover data. Societal expectations regarding naturalness in visuals, descriptions, presence of recreation facilities, and their interconnection were analyzed and presented. Binary regression analysis identified potential predictors of visual preferences. Results showed a high preference for mixed forests with a medium level of visual penetration and a moderate amount of natural deadwood. The results of the association between forest visuals and naturalness descriptions revealed societal expectations for closer-to-nature forests while still valuing the ability to explore and walk within them. Educational, visible signs and accessible paths were generally considered essential recreational facilities by the respondents, whereas sports amenities, kiosks, and parking areas were not. Frequent forest attendance and an age range from 18 to 45 years were primary indicators for visual preferences. Additionally, respondents residing in municipalities with over 20,000 inhabitants and those in Prague-Central Bohemia showed strong preferences for mixed stands and moderate natural deadwood occurrence, respectively. Understanding how socio-demographic attributes influence visual preferences can help tailor forest recreational services to specific target groups within Czech society.